Le Grand Inquisiteur : Âme et corps - Caroline Julliot (Cahiers d'Études du Religieux- Recherches Interdisciplinaires)
This article aims to replace in the general philosophical and metaphysical context of the romanticism the particular shape of conversion represented through the character of the Great inquisitor - by showing in what it is constituted in total break with the historical truth.